The Use of Role-Play Cards to Improve Hospitality Vocational School Students’ Speaking Skills in Responding Guest Complaint - Rasendria Jalu Siswanto Yulianto; Koesoemo Ratih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to improve students’ speaking skills in handling guest complaints by using role-play cards. This research employed Classroom Action Research (CAR) conducted in three cycles involving students of a vocational high school in Surakarta. The data were collected through speaking tests, observations, questionnaires, and interviews. The results showed a significant improvement in students’ speaking performance across cycles. In Cycle I, the students’ average score was relatively low, indicating difficulties in vocabulary use, fluency, and confidence. In Cycle II, the average score increased significantly after the implementation of role-play cards supported by vocabulary and expression lists. In Cycle III, the students’ performance became more stable, with most students achieving high scores. The final scores in Cycle III were obtained by averaging the scores from the teacher and the researcher to ensure objective assessment. In addition, the findings revealed that students became more confident, active, and able to respond to guest complaints appropriately. Therefore, it can be concluded that role-play cards are effective in improving students’ speaking skills and classroom engagement.